Current Concepts of Neural Stem/Progenitor Cell Therapy for Chronic Spinal Cord Injury - Suzuki, Hidenori; Imajo, Yasuaki; Funaba, Masahiro; Nishida, Norihiro; Sakamoto, Takuya; Sakai, Takashi (Frontiers in Cellular Neuroscience, 2022)
Chronic spinal cord injury (SCI) is a devastating condition that results in major neurological deficits and social burden. It continues to be managed symptomatically, and no real therapeutic strategies have been devised for its treatment. Neural stem/neural progenitor cells (NSCs/NPCs) being used for the treatment of chronic SCI in experimental SCI models can not only replace the lost cells and remyelinate axons in the injury site but also support their growth and provide neuroprotective factors. Currently, several clinical studies using NSCs/NPCs are underway worldwide. NSCs/NPCs also have the potential to differentiate into all three neuroglial lineages to regenerate neural circuits, demyelinate denuded axons, and provide trophic support to endogenous cells. This article explains the challenging pathophysiology of chronic SCI and discusses key NSC/NPC-based techniques having the greatest potential for translation over the next decade.